2016
DOI: 10.2169/internalmedicine.55.6230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin K<sub>2</sub> for Glucocorticoid-induced Osteoporosis in Patients with Systemic Autoimmune Diseases

Abstract: Objective Vitamin K2 (menatetrenone) is an effective treatment for patients with postmenopausal osteoporosis. We herein performed a subanalysis of patients with systemic autoimmune diseases undergoing glucocorticoid therapy in our previous prospective study. Methods Sixty patients were categorized into a group with vitamin K2 treatment (n=20, Group A) and a group without vitamin K2 treatment (n=40, Group B). All patients were treated with bisphosphonates. Results Serum levels of osteocalcin and undercarboxylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…However, WNT5A is usually considered to promote osteoclast differentiation and prevent adipocyte differentiation (26). Genistein alone (27) and MK-4 alone (28,29) reportedly promote bone formation; however, in the current study, their co-administration appeared to be more beneficial as it allowed the maintenance of NOTCH2 and WNT5A mRNAs at the levels observed in the control cells.…”
Section: ------------------------------------------------------------contrasting
confidence: 53%
“…However, WNT5A is usually considered to promote osteoclast differentiation and prevent adipocyte differentiation (26). Genistein alone (27) and MK-4 alone (28,29) reportedly promote bone formation; however, in the current study, their co-administration appeared to be more beneficial as it allowed the maintenance of NOTCH2 and WNT5A mRNAs at the levels observed in the control cells.…”
Section: ------------------------------------------------------------contrasting
confidence: 53%
“…Shikano et al reported that VK2 improves the levels of bone turnover markers in autoimmune disease patients with glucocorticoid‐induced osteoporosis. Furthermore, Ebina et al reported that the CRP, MMP‐3 and DAS28‐CRP levels were significantly decreased after 3 months of VK2 treatment in rheumatoid arthritis patients.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies may be due to the high dietary intake of VK, which may have limited the ability to analyze the association between VK intake and fracture risk. On the other hand, Shikano et al [86] found that VK improved bone turnover markers, while it did not affect BMD and fracture after 1.5 years in patients with osteoporosis on bisphosphonate therapy. Other similar studies suggested that combined therapy with risedronate and VK2 could not prevent vertebral fracture incidence in postmenopausal osteoporosis [85,87].…”
Section: Study Population Interventions Results Referencementioning
confidence: 97%